EVOLUTION OF SUGAR BEET AND SUGAR PRODUCTION IN ROMANIA AFTER ITS ACCESSION INTO THE E.U. - Aurel-Florentin BADIU; Florentina BADIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
The paper presents an analysis of the evolution for sugar beet production and sugar beet extraction after Romania accesion in European Union. The analysis is based on the evolutions of areas, total and average yields per unit of area. The last period (2007- 2013) is compared to the previous period (2001-2006), utilised at reference. Also, it is performed in the four sugar factories respectively (SC AGRANA Romania SA, Sugar Factory Bod, SC sugar Oradea SA, sugar Ludus SA) and it was made for the 2007-2013 period, after the application of EU’s rules for sugar market. The study presents the evolution of the biological sugar content and white sugar content between the years 2007 and 2013 and it evaluates the variability of the way of achieving production quotas. The main conclusion imposed after the analysis is that the systems of sugar production from sugar beet are stabilized. Statistically multi-annual average deviation from the assigned quota is approx .2%. Annual variations of sugar production are set between (-) 15 % - (+) 43%, compared with the Romanian quota (104.688 tons white sugar).